2002
DOI: 10.1016/s0014-5793(02)03277-5
|View full text |Cite
|
Sign up to set email alerts
|

p38 mitogen‐activated protein kinase dephosphorylation is regulated by protein phosphatase 2A in human platelets activated by collagen

Abstract: Collagen and the cross-linked collagen-related peptide (CRP-XL) each induced platelet p38 mitogen-activated protein kinase (p38) phosphorylation after 2 min. Subsequent dephosphorylation occurred in platelets activated with collagen, but not with CRP-XL, demonstrating glycoprotein VI-independent regulation of p38. Okadaic acid and fostriecin, inhibitors speci¢c for protein phosphatase 2A (PP2A), blocked p38 dephosphorylation, and PP2A co-immunoprecipitated with phospho-p38. In addition, use of phenylarsine oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 37 publications
4
36
1
2
Order By: Relevance
“…We also have shown that tyrosine phosphatase inhibitors did not block p38 MAP kinase activity. This is in contrast to other reports that suggest that protein phosphatases act as negative regulators of MAP kinases (72,73). Taken together, these findings suggest that p38 MAP kinase and SHP2 mediate HCV-E2-and HIV-gp120-induced IL-8 production.…”
Section: Discussioncontrasting
confidence: 95%
“…We also have shown that tyrosine phosphatase inhibitors did not block p38 MAP kinase activity. This is in contrast to other reports that suggest that protein phosphatases act as negative regulators of MAP kinases (72,73). Taken together, these findings suggest that p38 MAP kinase and SHP2 mediate HCV-E2-and HIV-gp120-induced IL-8 production.…”
Section: Discussioncontrasting
confidence: 95%
“…SB203580, instead, increased pERK without inducing musclespecific gene expression. Note that SB203580 induced an increase in the levels of pp38, probably through the inhibition of a self-regulatory loop mediated by a p38-activated protein phosphatase 2A (Sundaresan and Farndale, 2002). Indeed, treatment of QMb-LA29 in DM at 351C with okadaic acid (100 nM), a specific inhibitor of protein phosphatase 2A, induced a significant increase in the level of p38 phosphorylation (not shown).…”
Section: Resultsmentioning
confidence: 90%
“…20 Consistent with the inhibition of collagen-induced platelet activation, 19 GPVI dimerization was blocked by PAO, a commonly used inhibitor of Tyr phosphatases. 26 Protein disulfide isomerase inhibition by PAO was ruled out by the absence of effect of bacitracin (3 mol/L) on 9E18 binding (data not shown).…”
Section: Discussionmentioning
confidence: 97%